Acquired bleeding disorders. (6th May 2022) - Tiede, Andreas; Zieger, Barbara; Lisman, Ton
Abstract: Acquired bleeding disorders can accompany hematological, neoplastic, autoimmune, cardiovascular or liver diseases, but can sometimes also arise spontaneously. They can manifest as single factor deficiencies or as complex hemostatic abnormalities. This review addresses (a) acquired hemophilia A, an autoimmune disorder characterized by inhibitory autoantibodies against coagulation factor VIII; (b) acquired von Willebrand syndrome in patients with cardiovascular disorders, where shear stress abnormalities result in destruction of von Willebrand factor; and (c) liver function disorders that comprise complex changes in pro‐ and anti‐hemostatic factors, whose clinical implications are often difficult to predict. The article provides an overview on the pathophysiology, diagnostic tests and state‐of‐the‐art treatment strategies. Abstract :